Physical, mechanical and structural properties of yttrium oxide doped zinc borate glasses - Afrizal, N.H.; Yahya, N.; Yusoff, N.M.; Kasim, A.; Hashim, A. (2020)
In this project, the nominal glass composition with the form of (55-x) H3BO3-45ZnO-xY2O3 (x = 0.0, 0.5, 1.0, 1.5, 2.0 and 2.5 mol%) are synthesized by melt quenching techniques. The effect of Y2O3 on physical, mechanical and structural properties of glasses have been investigated using different characterization techniques. The parameters like density, molar volume and oxygen packing density have been calculated. Based on the micro hardness study, it has showed the decreasing trend from 518.80 N.mm to 453.13 N.mm with an increasing of Y2O3 content from 0.0 mol% to 2.5 mol%. The structural features of the yttrium oxide doped zinc borate glass were studied via X-Ray Diffraction (XRD) to confirm the amorphous nature of glass and Fourier Transforms Infrared Spectroscopy (FTIR) has been done to obtain the band positions and functional groups. FTIR spectral studies were recorded in the 400-4000 cm wavenumber range at room temperature.